The importance of high school on the university students’ success in the subject of mathematics - Lubishtani, Feride Qorrolli; Avdylaj, Blerina Tafolli (Frontiers in Education, 2023)
This research examines the relationship between the high school, namely high school profiles, and the students' success during the elementary mathematics course. For the analysis of this relationship, a mixed methods case study was chosen as a research design. Instruments for collecting the data were a questionnaire and a semi-structured interview that provided the answers to the research questions. The sample consisted of 81 students (N=81) from the University of Applied Sciences in Ferizaj (Kosovo) who participated in the questionnaire, whereas 12 of them were also interviewed. The research results indicate that the high school prepares students sufficiently for elementary mathematics. Therefore, the high school profile makes the difference in the students’ success in the elementary mathematics course at the university.